A novel diffusion‐tensor MRI approach for skeletal muscle fascicle length measurements. Issue 24 (21st December 2016) - Oudeman, Jos; Mazzoli, Valentina; Marra, Marco A.; Nicolay, Klaas; Maas, Mario; Verdonschot, Nico; Sprengers, Andre M.; Nederveen, Aart J.; Strijkers, Gustav J.; Froeling, Martijn
Abstract: Musculoskeletal (dys‐)function relies for a large part on muscle architecture which can be obtained using Diffusion‐Tensor MRI (DT‐MRI) and fiber tractography. However, reconstructed tracts often continue along the tendon or aponeurosis when using conventional methods, thus overestimating fascicle lengths. In this study, we propose a new method for semiautomatic segmentation of tendinous tissue using tract density (TD). We investigated the feasibility and repeatability of this method to quantify the mean fascicle length per muscle. Additionally, we examined whether the method facilitates measuring changes in fascicle length of lower leg muscles with different foot positions. Five healthy subjects underwent two DT‐MRI scans of the right lower leg, with the foot in 15° dorsiflexion, neutral, and 30° plantarflexion positions. Repeatability of fascicle length measurements was assessed using Bland–Altman analysis. Changes in fascicle lengths between the foot positions were tested using a repeated multivariate analysis of variance (MANOVA). Bland–Altman analysis showed good agreement between repeated measurements. The coefficients of variation in neutral position were 8.3, 16.7, 11.2, and 10.4% for soleus (SOL), fibularis longus (FL), extensor digitorum longus (EDL), and tibialis anterior (TA), respectively. The plantarflexors (SOL and FL) showed significant increase in fascicle length from plantarflexion to dorsiflexion, whereas the dorsiflexors (EDL and TA) exhibited a significant decrease. The use of a tract density for semiautomatic segmentation of tendinous structures provides more accurate estimates of the mean fascicle length than traditional fiber tractography methods. The method shows moderate to good repeatability and allows for quantification of changes in fascicle lengths due to passive stretch. Abstract : Diffusion‐Tensor MRI (DT‐MRI) is able to reconstruct complex 3D muscle architecture and provide quantitative information on muscle (micro) structure, including pennation angle and fascicle curvature. However, the measurements of fascicle length has been proven more challenging. In this work, we propose a new method to quantify muscle fascicle length. Our method relies on semiautomatic tendon segmentation based on tract density. The fascicle length values found in our work are in agreement with previously published cadaveric data. Furthermore, the method proved to be repeatable and sensitive enough to detect changes in fiber length in the lower leg as a function of different foot position.